Asymmetric quasi impedance source buck-boost converter - Ado, Muhammad; Jusoh, Awang; Sutikno, Tole (Institute of Advanced Engineering and Science, 2020)
An impedance source buck-boost converter (BBC) prototype for renewable energy (RE) application in the transportation industry is proposed. Its functions include stabilizing the variable output voltage of the RE sources such as fuel cells and photovoltaic cells. The converter utilized a topology of DC-DC quasi-impedance source converters (q-ZSCs) to achieve the gain curve of the BBC. With BBC gain curve, the converter earned advantages over the two other classes of non-isolated DC-DC q-ZSCs. These advantages include ecient buck-boost capability at the ecient duty ratio range of 0:35-0:65 and continuous and non-zero gain at the ecient duty ratio range. The converter's q-ZSC topology implies using two capacitors and two inductors. These two capacitors and inductors formed two separate LC filters that provides second order filtering compared to the first order filtering in BBC. Its other advantages over the traditional BBC include elim-ination of dead and overlap-time, simple contol and permitting higher switching frequency operation. The converter is capable of utilizing high switching frequency and asymmetric components to achieve BBC gain by using smaller components to reduce cost, weight and size. Its simulation response and that of a correspond-ing BBC for some given specifications were compared, presented and analyzed. An experimental scaled-down prototype was also developed to confirm its operation. Analysis of the converters responses comfirmed the prototype's second order filtering as against the first order filtering in traditional BBC.